Social learning in environmental management : towards a sustainable future - Keen, Meg; Brown, Valerie A.; Dyball, Rob (Earthscan, 2005)
Social Learning in Environmental Management explores and expands the approaches to collective learning most needed to help individuals communities experts and governments work together to achieve greater social and ecological sustainability. It provides practical frameworks and case studies to assist environmental managers in building partnerships that can support learning and action on issues arising from human impacts on the life-support systems of our planet. In this book social learning frameworks and case studies address the three areas of collaboration community government and profession.